2015
DOI: 10.1093/ee/nvv099
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape Analysis to Understand Orientation of Honey Bee (Hymenoptera: Apidae) Drones in Puerto Rico

Abstract: Honey bees [Apis mellifera L. (Apidae, Hymenoptera)] show spatial learning behavior or orientation, in which animals make use of structured home ranges for their daily activities. Worker (female) orientation has been studied more extensively than drone (male) orientation. Given the extensive and large flight range of drones as part of their reproductive biology, the study of drone orientation may provide new insight on landscape features important for orientation. We report the return rate and orientation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Flight-age drones were collected at the entrance during peak flight period, 14:00 to 17:00 h in Puerto Rico ( Galindo-Cardona et al, 2012 ). To collect these drones, we blocked the colony entrance with a queen excluder rather than the mesh used in worker collection ( Benatar et al, 1995 ; see also Galindo-Cardona et al, 2012 , 2015 ). In this way, we assured worker flow was not disturbed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flight-age drones were collected at the entrance during peak flight period, 14:00 to 17:00 h in Puerto Rico ( Galindo-Cardona et al, 2012 ). To collect these drones, we blocked the colony entrance with a queen excluder rather than the mesh used in worker collection ( Benatar et al, 1995 ; see also Galindo-Cardona et al, 2012 , 2015 ). In this way, we assured worker flow was not disturbed.…”
Section: Methodsmentioning
confidence: 99%
“…However, later in the season when drone production was greatly reduced, we collected drones from inside the colonies by opening the hives and extracting drones directly from the combs with the modified vacuum. Drones collected later in the season would be flight-age individuals ( Galindo-Cardona et al, 2012 , 2015 ). When an adequate number of drones were collected with either approach, they were taken to the laboratory for testing as with workers.…”
Section: Methodsmentioning
confidence: 99%
“…For the first few days afterwards, young drones interact with workers near the brood area to be fed and groomed (Goins and Schneider 2013;Collison 2004). Orientation flights, which help drones learn the local landmarks and precise location of the nest, begin approximately 5 to 8 days following emergence (Tofilski and Kopel 1996;Collison 2004;Galindo-Cardona et al 2015). Once a drone has learned the main landmarks and location of the hive, his life cycle culminates when he joins a drone congregation area ("DCA") with a diameter of 30 to 200 m (Loper et al 1987(Loper et al , 1992Koeniger and Koeniger 2004), where as many as 11,000 drones gather midair at between 10 and 40 m above ground (Free 1987;Baudry et al 1998;Koeniger et al 2005a).…”
Section: Reproductive Behaviormentioning
confidence: 99%
“…There is indication that factors such as vegetation structure, directionality, and density affect drone flight navigation (Galindo-Cardona et al 2012. In one study, drones showed either enhanced or limited navigational abilities based on cardinal direction and distance, with some exhibiting higher rates of return to their colony from greater distances when returning from the north or south, but not having the ability to return from distances of 4 km or more when returning from an eastern direction (Galindo-Cardona et al 2015).…”
Section: Reproductive Behaviormentioning
confidence: 99%
“…After learning the location of their hive, drones search for DCAs [ 6 ], and after doing that they return to their hives or drift to other hives to feed [ 7 , 8 ]. Their orientation and return to the original hive and apiary depend on the characteristics of the landscape, such as cardinal points and slope [ 9 ]. The flights in search of DCAs have a longer duration (more than 30 min) than the orientation flights.…”
Section: Introductionmentioning
confidence: 99%